2007
DOI: 10.1021/np0702281
|View full text |Cite
|
Sign up to set email alerts
|

Trypanocidal and Antileishmanial Dihydrochelerythrine Derivatives from Garcinia lucida

Abstract: Three benzo[ c]phenanthridine alkaloids have been isolated from the stem bark of Garcinia lucida: dihydrochelerythrine ( 1), 6-acetonyldihydrochelerythrine ( 2), and its new derivative, ( S)1''-(9,10-dihydro-2',3'-dihydroxy-7,8-dimethoxy-10-methyl-1,2-benzophenanthridin-9-yl)propan-2''-one (lucidamine A) ( 3). The new diisoprenylated derivative of lucidamine B ( 4) was obtained by semisynthesis. These dihydrochelerythrine derivatives as well as the crude extract displayed attractive antiprotozoal activity agai… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
34
0

Year Published

2009
2009
2019
2019

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 69 publications
(36 citation statements)
references
References 16 publications
0
34
0
Order By: Relevance
“…18 Previous publications, 17,18 however, reported the isolation of the unstable parent alkaloids avicine and nitidine. Although acetone derivatives of avicine and nitidine have been reported in the literature, [19][20][21] as well as acetone aducts of two other benzophenantridine alkaloids, 22,23 it is controversial, however, whether those acetone derivatives are really present on the plant extract or were isolated as artifacts, due to the greater stability of the acetone aducts as compared to the parent alkaloids avicine and nitidine. …”
Section: Resultsmentioning
confidence: 99%
“…18 Previous publications, 17,18 however, reported the isolation of the unstable parent alkaloids avicine and nitidine. Although acetone derivatives of avicine and nitidine have been reported in the literature, [19][20][21] as well as acetone aducts of two other benzophenantridine alkaloids, 22,23 it is controversial, however, whether those acetone derivatives are really present on the plant extract or were isolated as artifacts, due to the greater stability of the acetone aducts as compared to the parent alkaloids avicine and nitidine. …”
Section: Resultsmentioning
confidence: 99%
“…To our knowledge, there was no previous report on the antimicrobial activities on beta-lactamresistant bacteria or the chemical natures of the potentially antimicrobial compounds of the 12 plant species investigated in the present study. However, some studies revealed the presence of bergapten, coumarin, beta-sitosterol, beta-sitosterol glucopyranoside, oleanolic, naringenic acid, and prorepensin in D. picta [22]; flavonoids and xanthones in G. kola [23,24], cycloartane derivatives, anthocyane, flavonoids, saponins triterpenes and alkaloids in G. lucida [25][26][27], friedelin, taraxerone, epifriedelinol, taraxerol in B. micrantha [28,29], sterols in P. africanus [30]. It is probable that some of these compounds, alone or in combination, are responsible for the observed antimicrobial properties as previously shown.…”
Section: Discussionmentioning
confidence: 99%
“…Concerning the safety of the plants studied, G. lucida has little toxicity to Vero cells and the host cells [25], whereas the extract of B. micrantha is cytotoxic and possess acute systemic toxicity [34].…”
Section: Zenkerimentioning
confidence: 99%
“…Antiplasmodial (IC 50 , µg/ml) and cytotoxic (CC 50 , µg/ml) activities, and selective index of samples from B. sumatrana leaves against chloroquine-sensitive NF54 and chloroquine-resistant K1 strains of P. falciparum (IC 50 , µg/ml). complex composition, purification might lead to the isolation pure compounds with highly increased activity.…”
Section: Antiprotozoal and Cytotoxic Effectsmentioning
confidence: 99%
“…In the cytotoxic studies, it was observed that except ME-1.3 and ME-1.4 samples devoid with cytotoxic effect against MRC-5 cell line (CC 50 > 64 and 34.24 µg/ml respectively) since their CC 50 are greater than 32 µg/ml, the remaining samples were cytotoxic with CC 50 values ranged from <0.25 to 24.05 µg/ml since their respective CC 50 were weaker than 32 µg/ml [17].…”
Section: Cytotoxic and Selective Effects Of Samples Of B Sumatrana Lmentioning
confidence: 99%